Kecukupan Nutrien dan Prevalensi Parasit Cacing pada Sapi Bali di Lahan Gambut - Adrial Adrial; Rudy Priyanto; Salundik Salundik; Iwan Prihantoro (Jurnal Ilmu Pertanian Indonesia, 2020)
Peatlands have specific characteristics with waterlogged conditions, fragile, and less fertile. The level of peatlands fertility dependent on depth peat and the distance from rivers. This study was aimed to evaluate nutrient adequacy and prevalence of worm infestations in the gastrointestinal tract of Bali cattle that maintained in different peatland categories. The research was conducted in Pulang Pisau District, Central Kalimantan. The site was determined by purposive sampling and divided into 3 categories peat swamp, shallow peat near the river, and shallow peat away from the river. The data were collected by survey method and laboratory analysis. The variables observed included forage quality, nutrient intake, the number of infected cows, and the number of eggs per gram of feces (EPG). The results showed that each category of peatland have different feed quality and nutrient adequacy (P<0.05). The nutrient intake in the peat swamps was relatively higher than that of other sites. In general, the nutrient adequacy of cattle raised in the peatlands area was still below the standard requirement. In all peatland categories, the occurring of Ca deficiency in the diet was pronounced. The highest prevalence of parasitic worms infection was found in cows raised in peat swamps. Bali cattle that maintained in different peatland categories generally showed different responses in nutrient adequacy and prevalence of parasitic worms infection. Keywords: Bali cattle, nutrient adequacy, parasitic worm, peatlands, prevalence